Two new species of Diastatotropis Lacordaire from protected areas in central and east Madagascar (Coleoptera: Anthribidae) - Trýzna, Miloš; Blažej, Lukáš; Rakotonirina, Jean Claude (Zootaxa, 2024)
Two new species, Diastatotropis lusti Trýzna, Blažej & Rakotonirina sp. nov. and Diastatotropis petulae Trýzna, Blažej & Rakotonirina sp. nov. (Anthribidae: Anthribinae: incertae sedis), from Madagascar are described, including colour habitus photographs, drawings of male and female genitalia, ecological notes and photographs of the habitat.